Relationship Between Emotional Intelligence With Stress Level of First Year Student in Nursing Program Study Medical Faculty Hasanuddin University - Muhnia Muhnia; Wa Ode Nur Isnah; Hapsah Hapsah (Faculty of Nursing, Universitas Hasanuddin, 2018)
Introduction: Stress is a thing that can be experienced by anyone, including first year students. Every person are different in coping with stress, one of the factor is emotional intelligence. This study aimed to investigate the relationship between emotional intelligence and stress level of first year students in Nursing Program Study Medical Faculty Hasanuddin University. Method: The study design was cross sectional approach. This research was conducting by filling the quostionnaire of emotional intelligence and stress, are measured by emotional intelligence adolescent and Depression Anxiety Scale (DASS 42).Result: In this study showed that there is a relationship between emotional intelligence and stress level of first year students, with significant value of p 0.036. Individual with high emotional intelligence, showed the lower stress level. The dimensions of emotional intelligence that may have be contributed to the stress of students are ability to manage emotions and motivation. Conclusions: It is concluded that there is a negative relationship between emotional intelligence and stress level of first year students. Therefore, it is necessary to have a program that can develop emotional intelligence for first year student.